Physical Violence during Pregnancy and Its Implications at Birth: Analysis of a Population Survey, 2019 - Medrano, Laura Virginia Periche (2023)
Physical partner violence is widely recognized as a global health problem, especially in pregnant women. This study determines the association between physical violence during pregnancy in Peruvian women aged 15 to 49 years with low birth weight and abortion according to the Demographic and Family Health Survey (ENDES) 2019. An analytical cross-sectional observational study was carried out based on the data from the ENDES 2019. Two dependent variables referring to birth outcomes were included: abortion and low birth weight. The independent variable was physical violence during pregnancy by her current or former husband/partner. A total of 15,305 women were included in the study. The prevalence of physical violence during pregnancy was 6.43%. Regarding the adverse outcomes of pregnancy, the prevalences of abortion and low birth weight were 20.84% and 6.01%, respectively. Women suffering physical violence during pregnancy were more likely to have an abortion but not low birth weight. In conclusion, it was found that 6 in 100 Peruvian women of childbearing age were victims of violence during pregnancy. Likewise, it was observed that women who were victims of violence during pregnancy had a higher probability of having an abortion but not low birth weight.